Information Technologies in the Tourism Industry - Odilovich, Rakhimov Zafar; Uktamovich, Djurakulov Xusen (Research Parks Publishers, 2023)
The article deals with the tourism industry, which is widely implementing technological innovations to meet the needs of its customers. In organizations and institutions, information systems are responsible for computers, networks, and data management. The use of technology in the hospitality and tourism industry has helped speed things up and make travel more enjoyable and efficient. Technology helps not only large chain hotels, but can also be useful for smaller companies in the industry.